2009
DOI: 10.1093/njaf/26.3.99
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Browsing, Seedbed, and Competition on the Development of Yellow Birch Seedlings in High-Graded Stands

Abstract: Many hardwood or mixedwood stands of northeastern North America have been high graded in the past and need restoration treatments to bring them back to an acceptable level of production. Even when early seedling establishment can be secured, further development may be compromised bymany factors. This study looks at the effect of seedbed, browsing, and competition on the growth and survival of yellow birch (Betula alleghaniensis Britt.) seedlings that became established after a brushing and scarification treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Scarification techniques that expose larger areas of bare mineral soil, like disc trenching in continuous rows, increase the establishment of birch seedlings to densities that might be suitable for establishment of mixed forests. Consistent with earlier studies, the study showed that not only the disturbance rate per se but also the type of scarification affects the regeneration success (Elie et al, 2009;Prevost et al, 2010) and the species composition (Prevosto et al, 2011). However, the scarification effect on a specific site may not be sufficient for predicting the regeneration success.…”
Section: Discussionsupporting
confidence: 86%
“…Scarification techniques that expose larger areas of bare mineral soil, like disc trenching in continuous rows, increase the establishment of birch seedlings to densities that might be suitable for establishment of mixed forests. Consistent with earlier studies, the study showed that not only the disturbance rate per se but also the type of scarification affects the regeneration success (Elie et al, 2009;Prevost et al, 2010) and the species composition (Prevosto et al, 2011). However, the scarification effect on a specific site may not be sufficient for predicting the regeneration success.…”
Section: Discussionsupporting
confidence: 86%